Вірджинія Вульф: людина у бутті і життя як творчість - М’ясоїд , Катерина (Психологія і суспільство, 2024)
У статті аналізуються дані, отримані у річищі Wulf Studies, досліджуються тексти щоденника, автобіографії Вірджинії Вулф, стилістика та семантика її роману To the Lighthouse. Методологією дослідження слугує культурологічний підхід у лінгвістиці Анни Вежбицької та у психології Володимира Роменця, а також концепція мислевчинення Анатолія В. Фурмана. Конкретизується тематизм, за яким у продукті культури об’єктивується намагання творчої індивідуальності збагнути смисл буття. Обстоюється положення, що це індивідуалізований вчинок, логічні і психологічні моменти якого проливають світло істини на особливості людського самопізнання. Показується, що в одиничному віддзеркалюється всезагальне, що буття промовляє словами присутньої у ньому людини, а та вчинковим способом своєї ось-буттєвості оповідає про саме буття і про своє місце в ньому. В. Роменець осягає присутність людини у бутті абстрактним, В. Вулф – образним мисленням. Відтак постають теорії буття, об’єднані ідеєю психічного як невід’ємного аспекту олюдненої безконечності. Воднораз аналізується погляд А. Снайт про вираження індивідуальності В. Вулф у публічному і приватному вимірах непрямого внутрішнього монологу в її романах. Перевіряється гіпотеза, за якою і в стилістиці, і в семантиці текстів письменниці знаходить відлуння її власний голос у формі теорії безпосередньої присутності людини у бутті. Остання постає на підґрунті її, зумовленої несприятливими обставинами дитинства, надміру загостреної чутливості. Заперечуються спроби схарактеризувати творчість В. Вулф у термінах психічної хвороби. Викладаються ідеї теорії: життя людини є таким, яким вона його відчуває, сприймає, пригадує; відчуття особи – маркери буттєвости як справжньої реальности, що заявляє про себе у певні моменти повсякдення й через неї виражає себе; час зупиняється, людина відчуває свою присутність у всезагальному; всезагальне відображається фрагментарно, має вигляд її власного витвору, хоча таким творінням є вона сама. Констатується відмінність задумів В. Вулф від концептів А. Берґсона: письменниця описує олюднене, а філософ – “чисте” буття. Відзначається спорідненість ідей письменниці з ідеями М. Гайдеґґера й стверджується, що словами непрямого внутрішнього монологу в її творах промовляє саме буття у його індивідуалізованому вираженні. Аргументується, що сформульована гіпотеза знаходить підтвердження: у романі В. Вулф To the Lighthouse, і в стилістиці, і семантиці непрямого внутрішнього монологу, оприявнюється теорія безпосереднього існування людини у бутті. Поряд із різноголоссям промовляє її власний голос. Концепти роману Window, Time passed, Lighthouse, Water, Death передають низку значень: людина начебто через вікно свого будинку дивиться на реальність; час залишається в минулому; реальність губиться у далині, кличе, проте зостається недосяжною; життя людини – начебто хвилі моря, що розмивають землю, царина повсякдення невідворотно зменшується … Концепти – складові теорії екзистенційного уприсутнення людини в ось-бутті В. Вулф. Висловлюється припущення, що художниця Лілі Бріско в романі To the Lighthouse – це сама В. Вулф. Зосереджується увага на словах В. Вулф про непереборне бажання художниці стрибнути у воду і потонути. Через 13 років письменниця здійснює самогубство саме таким чином. У цьому романі закодовані і життя авторки, і її кроки назустріч смерті. Крім того, виокремлюється базовий ґештальт теорії В. Вулф – образ квітки, що падає на землю. Бачене в дитинстві породжує відчуття моменту існування конкретного у безмежному, набуває теоретичного оформлення і стає концептуальною засадою творчості. Те, що зринає у підсвідомому, стає образом свідомости, котрий категоризується й визначає спосіб творчості, де персоніфікована креативність постає свідченням того, що людське самопізнання здійснюється унікальним, проте закономірним, чином.The article analyzes the data collected in the field of Woolf Studies, explores the texts of Virginia Woolf’s diary, autobiography, as well as the stylistics and semantics of her novel To the Lighthouse. The research methodology draws on Anna Vezhbitskaya’s theory of linguistic semantics, Vladimir Roments’s theory of deed, and Anatoly Furman’s concept of thought formation. The author asserts that the product of culture represents the attempt of a creative individual to grasp the meaning of being. It is argued that this is an individualized deed, where its logical and psychological shed light on the peculiarities of human self-knowledge. The analysis demonstrates that the individual mirrors the universal and being is expressed through an individual present in it; through the deed of being, a human communicates about being and their role within it. V. Romenets explores the presence of a human in being through abstract thinking, while V. Woolf approaches it through figurative thinking. Similar theories of being arise, all linked by the idea of the psychic as an integral aspect of humanized infinity. The article examines A. Snaith’s perspective on how Virginia Woolf’s individuality is expressed through the public and private voices of indirect interior monologue in her novels. The hypothesis being tested posits that both the style and semantics of Virginia Woolf’s texts contain her own voice in the form of the theory of the direct presence of a human in being, which arises based on her overly acute sensitivity due to the challenging circumstances of her childhood. Attempts to label the writer’s work as a manifestation of the illness are contested. The ideas of the theory are summarized: human life is defined by how an individual feels, perceives, and remembers it; human sensations are markers of being as a true reality; the latter declares itself at certain moments of life and expresses itself through a human; time stops, a human feels his or her presence in the universal; the universal is reflected in fragments, appearing as his or her own creation, although such a creation is himself or herself. The difference between the ideas presented by V. Woolf and A. Bergson is explained: while the writer depicts being in a humanized form, the philosopher discusses a “pure” form of being. The author observes the connection between the writer’s ideas and those of M. Heidegger, arguing that the expressions found in an indirect interior monologue of her works are manifestations of being in its individualized expression. The hypothesis is substantiated: in V. Woolf’s novel To the Lighthouse, both the stylistics and semantics of the indirect interior monologue illustrate the theory of the direct presence of a human in being. Alongside with the public and private voices (A. Snaith), her own voice is present. The concepts identified in the the novel: Window, Time, Lighthouse, Water, and Death convey the following meanings: an individual perceives reality through the window of their house; time persists in the past; reality is lost in the distance, beckons yet remains unattainable; and human life is likened to the sea waves that gradually erode the earth, the life domain is inevitably vanishing in the novel... The concepts discussed are components of V. Woolf’s theory of the direct presence of human in being. The character, artist Lily Briscoe in the novel To the Lighthouse is posited to represent V. Woolf herself. Focus is placed on the expressions used in an indirect interior monologue that reveals the artist’s compelling urge to leap into the water and drown. Notably, thirteen years later, the writer ended her own life in a similar manner. Consequently, the novel appears to encode both the trajectory of V. Woolf’s life and her approach to her eventual death. The basic gestalt of V. Woolf’s theory is the imagery of a flower falling to the ground. Childhood perceptions shape a sense of the moment of being of the concrete in the infinite, which subsequently adopt a theoretical framework, and becomes the conceptual foundation for creativity. What emerges in the subconscious evolves into the image of consciousness, and the latter is categorized and determines the creativity trajectory. This process demonstrates that human cognition of oneself occurs in a distinctive yet systematic manner.